Membangun Konsep Brand Religiosity Image Dalam Islamic Marketing (Sintesis Teori dan Penelitian Empiris yang Relevan) - Munadi Idris; Haris Maupa; Mahlia Muis; Maat Pono (ITB AAS INDONESIA Surakarta, 2020)
The concept of Islam in marketing is elastic. Everything can be done unless there is a prohibition and this is only in the smallest parts. This is one of the causes lately, experts in marketing are interested in the concept of Islamic marketing. In the aspect of brand image, Islam has its own uniqueness that is able to attract customers not only materially but also emotionally, so that customers will always be loyal to brands that have that Islamic image. This paper is library research that aims to produce a concept in Islamic marketing that is sourced from the study of grand and middle theories or previous empirical research. This paper tries to synthesize theories based on appropriate theoretical concepts then harmonize with the concept of Islamic marketing and will produce research findings